Physiological differences in aerobic performance (VO^2 max) and recovery between men and women - Çaushi, Alketa; Ikonomi, Edison (Edelweiss Applied Science and Technology, 2025)
Gender differences in exercise performance and recovery are influenced by physiological and hormonal factors. This study investigated these differences in an 8-week aerobic training program, focusing on VO₂ max, heart rate, calorie expenditure, and recovery time. Sixty healthy adults (aged 25-40), equally divided by gender, participated in the study. All participants maintained a baseline fitness level and had no history of cardiovascular or metabolic disorders. Results showed that men experienced a 15% improvement in VO₂ max, compared to 10% in women, suggesting greater cardiovascular adaptations. Men also burned 20% more calories per session than women, likely due to their higher muscle mass and basal metabolic rate. However, women demonstrated faster recovery times, returning to baseline heart rates within 10-12 minutes, while men required approximately 15 minutes. This difference may be attributed to hormonal influences, particularly estrogen’s role in cardiovascular recovery. Both genders exhibited reductions in resting heart rate, with a more significant decrease observed in men. These findings emphasize the need for gender-specific training approaches. Men may benefit from high-intensity training to maximize endurance and cardiovascular adaptations, whereas women may achieve better results by incorporating endurance-based and recovery-focused exercises. Personalized training programs that account for these physiological differences can optimize performance outcomes for both sexes. Further research into hormonal effects on exercise response is recommended to refine gender-adapted training strategies, improving athletic performance and recovery.